The impact of socio-economic and human behavioural factors on the water of the Fontein Spruit catchment : a water management model study in a developing community - Pretorius, Elizabeth (University of the Free State, 2002)
A world water crisis has been predicted as early as 1977 and since then, water professionals call this coming crisis to the attention of the world community at various conferences, summits and congresses. Recent assessments conducted for the United Nations and for the World Commission on Water indicated that almost half a billion people face water shortages in 29 countries and by 2025, almost two-thirds of the people are forecast to experience some form of water stress. Although this global water crisis tends to be viewed as a water quantity problem, water quality is increasingly being acknowledged as an important factor in water scarcity. In many developing countries water quality has become the principal limiting factor to water availability. The water quality situation in developing countries is highly variable reflecting social, economic and physical factors, state of development as well as climatic and geographical factors. In recent years several studies have been done in South Africa to determine the quantitative and qualitative characteristics of urban runoff and their impact on receiving waters. These studies suggest that there was a large difference in the type of pollutants that were observed in the receiving waters and that the major factor affecting the type of pollution is the type of development that the catchment is undergoing. The studies conducted on the high-density informal settlements imply that any form of urban development that includes shacks and/or informal houses will have a detrimental effect on the quality of urban runoff. Low-cost, high-density type urbanisation, with its informal housing and shack areas, is an inescapable part of South Africa and will continue to play a major role in this country for many years to come. In recent years, South Africa has experienced a massive increase in urbanisation, a large proportion of which takes the form of high-density, informal settlements that developed around existing metropolitan areas. Based on current patterns of growth, the extent of this form of urbanisation is predicted to treble within 20 years. This rapid growth of urban areas in South Africa has been accompanied by increased quantities of contaminated urban runoff and this, in turn, has accelerated the degradation of streams, rivers, lakes and estuaries. Urban runoff acts as an efficient transport mechanism for bacteria, viruses, nutrients, organic substances, heavy metals and other pollutants. Alone or in combination, these substances cause water quality problems, pose potentially serious risks to human- and environmental health through contact recreation and through the use of untreated water. Therefore, it is vitally important that the scientific and engineering society continue to study these urban catchments and to develop new and innovative ways of dealing with the problems associated with urban runoff. The study area provided a unique opportunity for the investigation, implementation and evaluation of an integrated water quality management programme, as it is a typical example of a community with rapid, largely uncontrolled, growth of low-cost, high-density housing developments. The research project was primarily aimed to gain a better understanding of the major causes of pollution in the study area, and once the principle contributing factors had been identified and investigated, a Water Quality Management Plan was developed. The research project was based on the assumption that water quality problems arising from developing communities can be managed using an integrated approach to ensure that the receiving water environmental objectives can be met on a sustainable basis and that the management practices and interventions to deal with pollution problems from developing communities can be sustained by addressing the socio-economic and human behavioural factors contributing to the problems. The Water Quality Management Plan is therefore an integrated plan addressing the management of water quality in the community in the study area, and also permits the extrapolation of the results to catchments with similar land use and human activities, locally as well as regionally.

'n Wereld water krisis is reeds vanaf so vroeg as 1977 voorspel en sedertdien het kundiges op die gebied van water hierdie komende krisis onder die aandag van die wereld gemeenskap tydens verskeie konferensies, berade en kongresse gebring. Onlangse beramings wat uitgevoer is vir die Verenigde Nasies en vir die Wereld Kommissie vir Water het aangedui dat bykans 'n half biljoen mense in 29 lande 'n water tekort in die gesig staar en teen 2025 word voorspel dat bykans twee derdes van die mense 'n vorm van water stres sal ervaar. Alhoewel daar geneig word om na hierdie wêreldwye water krisis te kyk as 'n water kwantiteit probleem, word water kwaliteit toenemend erken as 'n belangrike faktor in water skaarste. In baie ontwikkelende lande het water kwaliteit die hoof beperkende faktor vir water beskikbaarheid geword. Die water kwaliteit situasie in ontwikkelende lande is hoogs veranderlik en reflekteer sosiale, ekonomiese en fisiese faktore, stand van ontwikkeling sowel as klimaats en geografiese faktore. Verskeie studies is die afgelope jare in Suid-Afrika gedoen om die kwantitatiewe en kwalitatiewe eienskappe van stedelike afloop en hulle impak op die ontvangende water te bepaal. Hierdie studies stel voor dat daar 'n groot verskil is tussen die tipe besoedeling stowwe wat in die ontvangende water geidentifiseer is en dat die hoof faktor wat die tipe besoedeling bepaal, die tipe ontwikkeling is wat die opvanggebied ondergaan. Die studies wat uitgevoer is op die hoë digtheid informele nedersettings impliseer dat enige vorm van stedelike ontwikkeling wat tydelike en/of informele huise insluit 'n nadelige effek op die kwaliteit van stedelike afloop sal hê. Lae koste, hoë digtheid tipe verstedeliking, met sy informele en tydelike behuising gebiede, is 'n onvermydelike deel van Suid-Afrika en sal voortgaan om 'n belangrike rol in hierdie land te speel vir nog etlike jare. Suid-Afrika het in die afgelope jare 'n massiewe toename in verstedeliking ondervind waarvan 'n groot deel die vorm aanneem van hoë digtheid, informele nedersettings wat rondom bestaande metropolitaanse areas ontstaan het. Gebaseer op huidige groeipatrone word voorspel dat die mate van hierdie vorm van verstedeliking binne 20 jaar sal verdriedubbel. Hierdie vinnige groei van stedelike areas in Suid-Afrika word vergesel deur verhoogde hoeveelheid van besmette stedelike afloop en dit het die degraduering van strome, riviere, mere en riviermondings bespoedig. Stedelike afloop tree op as 'n doeltreffende vervoermeganisme vir bakterieë, virusse, voedingstowwe, organsiese stowwe, swaar metale en ander besoedelende stowwe. Hierdie stowwe, alleen of in kombinasie, veroorsaak waterkwaliteitsprobleme en hou potensiaal gevaarlike risikos vir menslike en omgewingsgesondheid in deur water kontak tydens rekreasie en deur die gebruik van onbehandelde water. Dit is daarom lewensbelangrik dat die wetenskaplike en ingenieurswese samelewing voortgaan om hierdie stedelike opvanggebiede te bestudeer en om nuwe en innoverende maniere te ontwikkel om probleme te hanteer wat geassosieer word met stedelike afloop. Die studiegebied het 'n unieke geleentheid voorsien vir die ondersoek, implementering en evaluering van 'n geïntegreerde water kwaliteitsbestuurprogram, aangesien dit 'n tipiese voorbeeld is van 'n gemeenskap met snelle, grootliks onbeheerde, groei van lae koste, hoë digtheid behuisingsontwikkelings. Die navorsingsprojek was primêr daarop gemik om 'n beter begrip van die hoofoorsake van besoedeling in die studiegebied te verkry, en nadat die hoofbydraende faktore geïdentifiseer en ondersoek is, is 'n Waterkwaliteitbestuursprogram ontwikkel. Die navorsingsprojek was gebaseer op die veronderstelling dat, eerstens, waterkwaliteitsprobleme wat onstaan uit ontwikkelende gemeenskappe bestuur kan word deur 'n geïntegreerde benadering te volg om te verseker dat die ontvangende water omgewingsdoelwitte bereik kan word op 'n volhoubare basis. Tweedens dat die bestuurspraktyke en ingryping om besoedelingsprobleme van ontwikkelende gemeenskappe te hanteer volhou kan word deur die sosio-ekonomiese en menslike gedragsfaktore wat bydra tot die probleem aan te spreek. Die Waterkwaliteitsbestuurplan is dus 'n geïntegreerde plan wat die bestuur van water kwaliteit in die gemeenskap van die studiegebied aanspreek en laat ook die ekstrapolering van resultate tot ander opvanggebiede met dieselfde landgebruik en menslike aktiwiteite, plaaslik sowel as streeksgewys toe.
Thesis (Ph.D. (Geography))--University of the Free State, 2002
Keywords: Water quality management -- South Africa; Water -- Pollution -- South Africa; Water quality management -- Environmental aspects -- South Africa